2006
DOI: 10.1590/s1413-82712006000100014
|View full text |Cite
|
Sign up to set email alerts
|

Comer ou não comer, eis a questão: diferenças de gênero na neofobia alimentar

Abstract: ResumoA neofobia alimentar é um comportamento de cautela quanto à ingestão de alimentos desconhecidos. Homens e mulheres apresentam diferenças comportamentais, embora as pesquisas sobre a resposta neofóbica apontem controvérsias. Neste estudo, 266 indivíduos realizaram uma tarefa de escolha entre dois alimentos, um familiar e outro não-familiar, e responderam a uma escala de neofobia, a fim de investigar as diferenças de gênero. Os resultados indicaram que as mulheres são mais neofóbicas que os homens, o que c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
(12 reference statements)
1
1
0
3
Order By: Relevance
“…This is in line with our study in which the food neophobics had, on average, a higher BMI than food neophilics; however, this relationship was more clearly observed in women than in men [20]. We did not find any differences in the level of food neophobia in terms of gender, which was also confirmed in previous studies [39,42], but some authors found that women are more neophobic than men [43,44], while others reported the contrary [10,16]. These differences in obtained results can be explained by the fact that food neophobia can be both inherited and environmentally conditioned [20,34], thus giving rise to cultural differences in the context of food between gender.…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with our study in which the food neophobics had, on average, a higher BMI than food neophilics; however, this relationship was more clearly observed in women than in men [20]. We did not find any differences in the level of food neophobia in terms of gender, which was also confirmed in previous studies [39,42], but some authors found that women are more neophobic than men [43,44], while others reported the contrary [10,16]. These differences in obtained results can be explained by the fact that food neophobia can be both inherited and environmentally conditioned [20,34], thus giving rise to cultural differences in the context of food between gender.…”
Section: Discussionsupporting
confidence: 93%
“…A neofobia alimentar apresenta importante papel na formação do hábito alimentar e vem sendo amplamente estudada em indivídu-os adultos 5,23 , principalmente devido à sua influência na variedade de alimentos consumidos 24,25 e de seu possível efeito na adesão a planejamentos dietoterápicos 26,27 . No estudo de Quick et al 28 envolvendo pacientes com diabetes mellitus tipo I foi observado que a neofobia alimentar estava negativamente associada à variedade da dieta dos participantes e também à adesão ao tratamento.…”
Section: Discussionunclassified
“…A amostra avaliada neste estudo foi predominantemente do sexo feminino, especialmente no curso de Nutrição, o que pode representar um fator importante nos achados do presente trabalho, pois estudos prévios com estudantes universitá-rios demonstraram que as mulheres apresentam maiores escores de neofobia alimentar 5 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…It is normally low after birth until the first year (breastfeeding period), rises from the age of 2 years onwards, peaks between 2 and 4.5 years, when children begin to gain autonomy in choosing their own food (Kral, 2018;Moding & Stifter, 2016), decreases during adolescence and stabilizes in adulthood, rising again slightly over time (Kral, 2018;Meiselman et al, 2010). Several other factors may be involved in neophobia, such as education, sex, income, workplace, where you live (urban or rural area), as well as the degree of nutritional information about food (Ferreira et al, 2017;Flight et al, 2003;Lopes et al, 2006;Meiselman et al, 2010). The influence of these factors on food neophobia can be assessed using instruments such as the Food Neophobia Scale (FNS) (Pliner & Hobden, 1992), used in adults.…”
Section: Evaluation Of Food Neophobia In Twinsmentioning
confidence: 99%